Athletes intending to use sports supplements are more likely to respond to a placebo - Hurst, P.; Foad, A.; Coleman, D.; ASt Beedie, C. (Medicine & Science in Sports & Exercise, 2017)
PURPOSE: We investigated associations between athletes' use of sport supplements and their responsiveness to placebo and nocebo interventions.